Financial Literacy and Saving Behavior: Global Cross-Sectional Evidence - António Afonso; Eduardo Rodrigues (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Savings play a critical role in both individual financial well-being and economic development. This article examines the impact of financial literacy, income, educational level, and age on saving decisions across 136 countries, using data from the Global Financial Inclusion Database (2021) and employing Generalized Structural Equation Modelling (GSEM). Financial literacy is conceptualized as a latent variable, based on five indicators related to financial knowledge, financial behavior, and financial attitudes, aligned with the Organization for Economic Co-operation and Development (OECD) pillars. The analysis demonstrates that financial literacy is a fundamental driver for saving in the short and long term. Education level and income are consistent predictors of savings, while age exhibits distinct effects depending on the savings objective. Regional differences emerge, with Latin American countries showing the strongest link between financial literacy and savings, whereas in high-income economies, its influence is less pronounced. These findings underscore the multifaceted role of financial literacy in shaping saving decisions and highlight its implications for tailored public policies.
Keywords: D14; G53; I22; C38; O16; 330; financial literacy; savings; Generalized Structural Equation Modelling; behavioral economics; global survey